Association of Risk Factors in Gestational Diabetes Mellitus among Pregnant Mothers Attending at a Tertiary Care Hospital in Bangladesh - Nusrat-Sultana; M A Hasanat; Sharmin-Jahan; Mashfiqul-Hasan; Yasmin-Aktar; Sandesh-Panthi; M Atiqur-Rahman; M Fariduddin (Journal of Bioinformatics And Diabetes, 2016)
Objective: To observe association of risk factors with gestational diabetes mellitus (GDM) in a tertiary care hospital of Bangladesh. Materials and Methods: Risk factors of GDM were evaluated in pregnant subjects (n=385; age: 26.4±4.9 yrs; body mass index, BMI: 25.3±4.3 kg/m2; mean ± SD) screened by 75 gram oral glucose tolerance test (OGTT) following WHO 1999 criterion irrespective of gestational age in the Department of Endocrinology, Bangabandhu Sheikh Mujib Medical University (BSMMU). BMI, maternal age, parity, trimester and family history of diabetes were considered as risk factors. Plasma glucose was measured by glucose-oxidase method on the same day. Results: GDM and normal glucose tolerance (NGT) showed significant difference for age (28.2±4.9 vs. 25.3±4.6 yrs, p<0.001), BMI (26.7±4.4 vs. 24.4±3.9 kg/m2, p˂0.001), family history of DM (55.5% vs. 43.0%, p=0.017) and number of gravida (p=0.048). There was no significant difference of frequencies of GDM among various trimesters (39.4% vs. 42.5% vs. 38.2%; χ2=0.653, p=0.721). OGTT performed before 24 weeks revealed GDM in about 44% (88/202). Multiple regression revealed age (p<0.001), BMI (p=0.007) and family history of DM (p=0.048) as independent predictors for GDM. Conclusion: It is concluded that age of mother, increased BMI, family history of diabetes as well as multigravidae are important predictors for GDM.
Keywords: GDM